Islamophobia and the Construction of Global Historiography:A Critical Analysis of the Representation of Islamic History in International Discourse - Halimi Najeeb Alkhawlani; Aljohani Mousa Qashqary; Mohamed Ibrahim Rejab; Abdelrazek Hasan Bin Zawawi; Daniel Jou (Yayasan Albahriah Jamiah Indonesia, 2026)
The rise in Islamophobic incidents following 21st-century geopolitical events has sparked debate about the representation of Islamic history in global historiography. Several studies have highlighted the dominance of conflict-oriented interpretive frameworks, but the relationship between Islamophobia, historical source selection, and the formation of global narratives has rarely been systematically examined. This study aims to identify patterns of representation of Islamic history, explain the mechanisms of historiographic construction, and examine the epistemological implications of Islamophobia in international historical literature. This literature review employs a qualitative approach, drawing on critical historiography and critical discourse analysis. The research corpus includes historiographic works published between 2001 and 2025, selected based on thematic relevance, citation influence, and a focus on global Islamic history. The analysis was conducted in the following stages: narrative classification, terminology identification, argumentation pattern tracing, dominant theme mapping, and epistemological framework interpretation. The results reveal three main tendencies: the dominance of narratives of conflict and Islamic political expansion; the marginalization of the intellectual, scientific, economic, and institutional contributions of the Islamic world; and the use of terminology that associates Islam with security threats and the clash of civilizations. The analysis also uncovered source selection practices that focused on Euro-Atlantic perspectives, neglected transregional networks of knowledge transmission, and limited use of Islamic primary sources. These patterns of representation reinforce the reproduction of stereotypes and narrow understanding of the complex history of Islamic civilization. These findings indicate the significant role of historiographical construction in shaping global perceptions of Islamic history and underscore the urgency of a reflexive, multi-perspective, and decolonial approach in contemporary historiographical studies.